How does cultural strategy drive the global expansion of edu-business? The case of a Japanese company in private supplementary education - Takamichi Asakura (Journal of International Cooperation in Education)
Purpose – This study aims to understand the mechanisms driving individuals to utilise and engage in edu-business and contribute to the industry’s development, even when they face criticism. To that end, this paper, focussing on corporate stories, explores the cultural strategies education companies employ to expand their businesses overseas. Design/methodology/approach – This paper examines the case study of Kumon Institute of Education, a key player in the Japanese edu-business sector. The analysis is based on interviews conducted between 2019 and 2021 with four public relations officers who possess extensive knowledge of the company’s history. Additionally, it draws on government and company documents, as well as newspaper articles. The analysis focusses on the narrative isomorphism between the company and the government from the provider’s perspective. Findings – Kumon’s corporate stories and narratives have been shaped by the history, culture and policies of Japan, its country of origin, rather than adopting a bottom-up approach or embracing neoliberal values. As the company expanded its international reach, its Japanese identity became a cornerstone of its narrative, heightening the appeal of its stories through the use of expert discourse and historic cultural resources. Recently, a synergy has developed between the public and private sectors in the realm of education export, reinforcing the distinctly Japanese nature of the company, which is particularly appealing to both users and employees. Originality/value – This paper focusses on the edu-business itself, analysing cultural strategies that go beyond the functional aspects of management or services to understand how edu-businesses have attracted people.